Personalizing Software Development Practice Using Mastery-based Coaching - BOESCH, Chris (Institutional Knowledge at Singapore Management University, 2014)
The authors previously developed a system to facilitate the self-directed learning and practicing of software languages in Singapore. One of the goals of this self-directed learning was to enable the development of student mentors who would then be able to assist other students during classroom sessions. Building on this work, the authors extended the platform to support personalized coaching with the goals of further enabling and preparing students to mentor their peers. This paper covers the challenges, insights, and features that were developed in order to develop and deploy this mastery-based coaching feature.